Education on the Utilization of Canva Apps to Improve Students' Digital Design Skills - Siti Aliyah; Efani Desi; Alan Akbar Bukhori; Muhatri; Enni Maisaroh; Sofyan Rahmad; Nabila Firka Hasibuan (Outline Publisher, 2026)
The development of digital technology requires students to master 21st century competencies, one of which is digital design skills. However, many students do not yet have adequate skills in utilizing graphic design applications to support learning. Therefore, an educational activity on the use of the Canva application was held at SMK Sinar Husni to improve students' knowledge, creativity, and skills in creating visual media. The method used is direct practice-based training (learning by doing) which includes the preparation stage, delivery of materials, practical assistance, and evaluation. This activity was attended by 23 students who received material on basic concepts of digital design, introduction to Canva, the use of templates, color arrangements, typography, graphic elements, as well as the creation of posters, presentations, and comics. The results of the activity showed that students experienced an increased understanding of the principles of visual design and graphic communication. All participants were able to produce digital design works that were more creative, interesting, and communicative than before the training. 100% active participation proves that Canva is an effective medium to support technology-based learning as well as an alternative to students' digital competency development programs.